Contract cheating by STEM students through a file sharing website: a Covid-19 pandemic perspective - Lancaster, Thomas; Cotarlan, Codrin (International journal for educational integrity, 2021)
Students are using file sharing sites to breach academic integrity in light of the Covid-19 pandemic. This paper analyses the use of one such site, Chegg, which offers “homework help” and other academic services to students. Chegg is often presented as a file sharing site in the academic literature, but that is just one of many ways in which it can be used. As this paper demonstrates, Chegg can and is used for contract cheating This is despite the apparent existence of an Honour Code on Chegg which asks students not to breach academic integrity. With pandemic led safety considerations leading to increased online teaching and assessment, the paper analyses data relating to how Chegg is used by students in five STEM subjects, namely Computer Science, Mechanical Engineering, Electrical Engineering, Physics and Chemistry. The results show that students are using Chegg to request exam style questions. They demonstrate that contract cheating requests can be put live and answered within the short duration of an examination. The number of student requests posted for these five subjects increased by 196.25% comparing the time period April 2019 to August 2019 with the period April 2020 to August 2020. This increase corresponds with the time when many courses moved to be delivered and assessed online. The growing number of requests indicates that students are using Chegg for assessment and exam help frequently and in a way that is not considered permissible by universities. The paper concludes by recommending that academic institutions put interventions in place to minimise the risk to educational standards posed by sites such as Chegg, particularly since increased online teaching and assessment may continue after the pandemic.